Implementasi Pop Up Book Dalam Meningkatkan Kecerdasan Linguistik Pada Anak Usia Dini - Masganti Sitorus; Nasution, Annisa; Sunya, Astri Syakira; Lubis, Mira Sinta (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research was conducted to find out about the implementation of pop up books in increasing linguistic intelligence in early childhood at RA Habibilla Jl. KUD Love the People. The data produced by this research was collected through analysis and observation. As well as using literature methods and telling stories through pop up books to children. The aim of research regarding the implementation of pop up books in increasing linguistic intelligence in early childhood really needs to be discussed, studied and applied to find out how the application of pop up books in increasing linguistic intelligence in early childhood is in accordance with intelligence development.